Innovation, gender, and labour productivity: Small and medium enterprises in Vietnam. (October 2021) - Hoang, Ngoc; Nahm, Daehoon; Dobbie, Michael
Highlights: This study finds that innovation increases firm labour productivity in Vietnamese SMEs. Female-controlled firms are not significantly less productive than male-controlled firms. Female-controlled firms are less likely to innovate than male controlled firms. Government assistance does not directly improve firm productivity. Government assistance does enhance firm productivity indirectly by increasing the probability of innovation. Abstract: This study undertakes an empirical analysis of the links between gender, innovation and firm labour productivity in Vietnamese Small and Medium Enterprises (SMEs). Specifically, we analyse whether female-controlled firms are more or less productive, than male-controlled firms. We also analyse whether female-controlled firms are more or less innovative than male-controlled firms. The present study goes further than most others in this area by allowing for endogenous selection into innovation, and by decomposing the productivity differential between innovators and non-innovators into the parts due to the differences in endowments and in technology. We show that while female-controlled firms are less likely to innovate, they are not less productive than male-controlled firms, once the role of innovation is controlled for. We also show that innovators are about 23% more productive than non-innovators, with over three quarters of this gap being due to innovators possessing better technology. An important contribution of our analysis is therefore to show that innovators are more productive than non-innovators mainly due to the use of different technology, not because they have better endowments. As the number of females starting or running new businesses is higher than males in developing countries, including in Vietnam, it follows that female entrepreneurship plays an important role in economic growth in emerging economies. Our analysis of the gender gap in business performance and innovation provides insights that assist with formulating entrepreneurship-related polices to assist this economic growth.